New bifunctional ionic liquid-based plant systemic acquired resistance (SAR) inducers with an improved environmental hazard profile. Issue 14 (29th June 2021) - Markiewicz, Marta; Lewandowski, Piotr; Spychalski, Maciej; Kukawka, Rafal; Feder-Kubis, Joanna; Beil, Stephan; Smiglak, Marcin; Stolte, Stefan
Abstract : SAR inducers with minimized environmental hazards and high biological activity are a step towards more sustainable agricultural practice. Abstract : Systemic acquired resistance (SAR) is a natural defence mechanism of plants against a broad range of pathogens. The induction of resistance is associated with the stimulation of plant metabolism that provides long-lasting beneficial effects to a variety of crop plants. SAR inducers are therefore an alternative to plant protection agents, which might reduce the use of pesticides or even substitute them. The known SAR inducer benzo[1, 2, 3]thiadiazole-7-carbothioic acid S -methyl ester (BTH) is poorly water soluble and therefore difficult to apply on the fields by spraying. It is much more soluble in water in the form of an ionic species derivative. The environmental hazard of BTH has been relatively well investigated, yet little is known about its ionic derivatives. In this study we tested ready biodegradability (mineralisation), cytotoxicity and aquatic toxicity (against luminescent bacterium Aliivibrio fischeri and water flea Daphnia magna ) of eleven BTH-derivatives that were prepared in our laboratories. None of the tested compounds proved to be readily biodegradable which is largely due to the fact that BTH itself is not biodegradable. Five compounds showed appreciable levels of degradation. The tested SAR inducers were characterized by a wide range of IC50 /EC50 values in cytotoxicity and (eco)toxicity tests indicating a highly diverse toxicity. However, a carboxylic acid derivative coupled with a cholinium cation showed a better environmental hazard profile than the parent compound due to higher, but probably only partial, biodegradability and lower toxicity. This compound was also shown to be a good SAR inducer.